Magnetic properties lithium-doped manganite single crystals - Barilo, S. N.; Bychkov, G. L.; Gatalskaya, V. I.; Kurochkin, L. A.; Sokol, V. P.; Szymczak, H.; Szymczak, R.; Baran, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Magnetic and resistivity properties of La1-xLixMnO3 single crystals with the perovskite structure atlithium concentrations x=0.06 and 0.2 are investigated over a broad temperature range at fields of upto 50 kOe. The Curie temperature is TC=90 K (x=0.06) and 300 K (x=0.2), respectively. Theelectrical resistance of the single crystal with x=0.06 increases steadily with temperature decrease, while the crystal with x=0.2 exhibits a magnetoresistance effect of ~ 8% at an external field of 9 kOe. The different dependence of the magnetizations MFC and MZFC of the sample with lower lithium contentin the temperature range below TC is associated with the formation of a cluster glass and is caused byhigh coercivity and magnetic anisotropy of the crystal.